Incidence of Public Spending on Economic Growth in South American Countries, 1995-2018 (2023)
The objective of this paper is to analyze the relationship between public spending directed to the education, health and research and development sectors, and the economic growth of South American countries, during the period 1995-2018. Given the structure of the data, a panel data model was estimated in its specifications of first differences, fixed effects, and random effects. When controlling for heteroscedasticity and serial autocorrelation, the result is that education spending is the only one that is positively influencing economic growth, while there is insufficient empirical evidence for spending in other sectors to affirm that it had an impact on the development of the South American economies.